Phenology and potential reproduction of turi (Sesbania grandiflora) at Cibinong, Bogor, Indonesia - Dida Syamsuwida; Aam aminah (Nusantara Bioscience, 2020)
Abstract. Syamsuwida D, Aminah A. 2020. Phenology and potential reproduction of turi (Sesbania grandiflora) at Cibinong, Bogor, Indonesia. Nusantara Bioscience 12: 13-20. Turi (Sesbania grandiflora (L.) Pers.) is one of a prospectus energy woody species to be developed in establishing renewable energy base forest plantation. The development of this species cannot be separated from the basic information of its reproductive biology. The study was aimed to evaluate flowering phenology and reproductive potency of S. grandiflora so that information could be elaborated to estimate the fruit production potential produced. The research method was carried out by direct observation of samples of flowering trees. Data were analyzed descriptively. The number of tree samples observed for flower and fruit development and reproductive success of 10 trees, from each tree were observed three flowering branches distinguished from the west and east branches. The results showed that S. grandiflora did not experience generative bud dormancy so that flower initiation was thought to occur throughout the year and could flower and bear fruit throughout the year. S. grandiflora at the observation location has a flowering-fruiting development cycle of about 3-4 months which begins with the emergence of generative bud at the time of the observation in April and developed into flower shoot in the same month. Blooming flower (anthesis) in May, develop into young fruit in June. Mature fruits can be harvested in June-July. The reproductive potency of S. grandiflora was low with a value of fruit set (fruit/flower ratio) at the eastern and western branches were 19% ± 0.07 and 17%±0.06 and seed set (seed/ovule ratio) of 87% ± 0.12 and 83% ± 0.16, respectively. Reproductive success was 18% ± 0.07 for the eastern branches and 17% ± 0.05 for the western branches. Most reproductive variables of S. grandiflora did not show a significant difference between the eastern and western branches (P>0.05), except for fruit number (P<0.05).